Picosecond nonlinearity of GeO2-Bi2O3-PbO-TiO2 glasses at 532 and 1,064 nm - Besse, Valentin; Fortin, Alexandre; Boudebs, Georges; Valle, Paula Squinca [UNESP]; Nalin, Marcelo [UNESP]; Araujo, Cid B. de (Springer, 2014)
The third-order optical properties of GeO2-Bi2O3- PbO-TiO2 glasses at 532 nm and 1,064 nm were studied to evaluate their potential for optical limiting and all-optical switching. The Z-scan technique was used to determine the nonlinear (NL) refractive index, n(2), and the NL absorption coefficient, alpha(2), of samples with different amounts of the constituent oxides. Values of n2 approximate to + 0.7 x 10(-1)4 cm(2)/W at 1,064 nm and approximate to + 1.5 x 10(-14) cm(2)/W at 532 nm were measured. The NL absorption coefficient, alpha(2), was smaller than the minimum that our apparatus can measure (alpha(2) < 0.01 cm/GW) in the near-infrared (1,064 nm); in the visible region (532 nm), we obtained alpha(2) approximate to 4.4 cm/GW. The set of NL parameters measured indicates the potential usefulness of the GeO2-Bi2O3-PbO-TiO2 glasses for all-optical switching at 1,064 nm and for optical limiting at 532 nm.